PENGARUH KEMANDIRIAN BELAJAR, CARA BELAJAR DAN BUDAYA MEMBACA TERHADAP HASIL BELAJAR - Rita Ismaya; R. Gunawan Sudarmanto; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This study aimed determine the effect of expected factor independence learning, how to learn, and culture of reading on the results of class XI IPS students studying Economics semester Perintis 2 Bandar Lampung State High School Academic Year 2012/2013.The results. (1).There a positive and significant influence independence learning the results of Class XI IPS students studying Economics Odd Semester Perintis 2 Bandar Lampung State High School Academic Year 2012/2013. (2).There a positive and significant influence on How to Learn Student Learning Outcomes Economy Class XI IPS Odd Semester Perintis 2 Bandar Lampung State High School Academic Year 2012/2013. (3).There a positive and significant influence on culture reading Student Learning Outcomes Economy Class XI IPS Odd Semester Perintis 2 Bandar Lampung State High School Academic Year 2012/2013. (4).There a positive and significant influence independence learning, How to Learn, and culture reading the results of Class XI IPS students Economics Odd Semester Perintis 2 Bandar Lampung State High School Academic Year 2012/2013.Keyword: Independence Learning, How to Learn, Culture of Reading, and Learning Outcomes